2021
DOI: 10.1002/ijop.12753
|View full text |Cite
|
Sign up to set email alerts
|

WillCOVID‐19‐related economic worries superimpose health worries, reducing nonpharmaceutical intervention acceptance in Germany? A prospective pre‐registered study

Abstract: N onpharmaceutical interventions (NPI) such as stay-at-home orders aim at curbing the spread of the novel coronavirus, SARS-COV-2. In March 2020, a large proportion of the German population supported such interventions. In this article, we analyse whether the support for NPI dwindle with economic worries superimposing virus-related worries in the months to follow. We test seven pre-registered 1 hypotheses using data from the German COSMO survey (Betsch, Wieler, Habersaat, et al. 2020), which regularly monitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
(66 reference statements)
2
11
0
1
Order By: Relevance
“…However, contrary to this hypothesis, perceived economic risk negatively predicted the observance of the rules. As conjectured by Rosman et al (2020) , our study revealed that individuals who fear economic losses to a greater extent were less stringent in observing the closure instructions of staying at home, refraining from work, and maintaining social distancing. This finding may makes sense thinking about the inherent conflicting interests between the precaution rules limitation and making a living, especially for young students.…”
Section: Discussionsupporting
confidence: 64%
“…However, contrary to this hypothesis, perceived economic risk negatively predicted the observance of the rules. As conjectured by Rosman et al (2020) , our study revealed that individuals who fear economic losses to a greater extent were less stringent in observing the closure instructions of staying at home, refraining from work, and maintaining social distancing. This finding may makes sense thinking about the inherent conflicting interests between the precaution rules limitation and making a living, especially for young students.…”
Section: Discussionsupporting
confidence: 64%
“…If individuals acknowledge the crucial role of scientists and public health experts in justifying COVID-19 related knowledge claims, they will, through increased safety and effectiveness beliefs, be more willing to become vaccinated against the disease. For this reason, science and public health communication should be a key element of each and every country's COVID-19 response strategy (see also Rosman et al, 2021). Openness and transparency have long been suggested as a central factor in building trust, which is why we would advocate for an honest, integer and transparent communication strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Rosman et al ( 2021 ) tested associations between COVID‐19‐related economic worries and virus‐related worries over the course of an unfolding pandemic. In a sample of 13094 Germans, virus‐related worries decreased over time, but economic worries remained largely stable.…”
Section: This Special Issuementioning
confidence: 99%